HUBUNGAN KEKERABATAN BAHASA SUNDA DAN MINANGKABAU: KAJIAN LINGUISTIK HISTORIS KOMPARATIF - Nur Yuannisa Luthfiah; Almanda, Adelia; Mutia, Sabrina Farah; Putra, Dona Aji Karunia (Universitas Hamzanwadi, 2026)
This study aims to identify the extent of kinship between the Sundanese and Minangkabau languages through a comparative historical linguistic approach. The scope of the study focuses on the analysis of basic vocabulary using a list of 200 Swadesh words. The method applied is a quantitative approach using lexicostatistical and glottochronological techniques to measure the percentage of cognates and estimate the time of separation of the two languages from a similar proto-language. The research data was obtained from credible lexical sources and compared based on similarities in form, phonemic variations, sound correspondence, and empty glosses. The results of the study show that the Sundanese and Minangkabau languages have a kinship level of 79%, placing them in the same language stock. Glottochronological analysis shows that the two languages are estimated to have diverged around 3,423–4,015 years ago, or around 1398–1990 BC. These findings indicate that the two languages originated from a single proto-language in the Western Austronesian language family and underwent regular phonological changes throughout their historical development.